2013
DOI: 10.4236/ojmm.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Characteristics of Men Attending Infertility Clinic of a Teaching Hospital

Abstract: The semen quality of 479 men in infertile marriages, who attended the infertility clinic of OOUTH, Sagamu between May 2004 and April 2009 were analyzed. The semen samples were physically examined, microscopically analyzed and aerobically cultured. The result showed that out of 51.5% oligospermic cases recorded, 39.8% could be classified severe. Cryptozoospermia were diagnosed in 72 (15%) cases. Bacteriospermia and Necrozoospermia were found in 149 and 6 cases respectively. The predominant organism isolated was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
0
7
1
Order By: Relevance
“…For sperm concentration, many studies have maintained a large and overlapping distribution in the fertile (control and subfertile) population (Lee et al, 2012; Levine et al, 2017 . Olajuba et al (2013) found that nearly 51.5% whose sperm concentration below 20×10 6 cell / ml could equally be a source or could contribute in infertility. In another study, 42.5 % of the subjects had a sperm count of less than 20× 10 6 cell / ml, while 53.2% had sperm motility of less than 50% (Loto, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For sperm concentration, many studies have maintained a large and overlapping distribution in the fertile (control and subfertile) population (Lee et al, 2012; Levine et al, 2017 . Olajuba et al (2013) found that nearly 51.5% whose sperm concentration below 20×10 6 cell / ml could equally be a source or could contribute in infertility. In another study, 42.5 % of the subjects had a sperm count of less than 20× 10 6 cell / ml, while 53.2% had sperm motility of less than 50% (Loto, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is the inability of a couple to conceive despite adequate, regular, unprotected intercourse of 12 months' duration [1]. On the other hand, male infertility is the inability of the male reproductive cells to produce mature, actively motile and functional spermatozoa in sufficient amount that will ensure fertilization of a released ovum in the fallopian tube [2]. Usually the women are blamed of infertile marriages, especially when the man is able to achieve erection and ejaculate [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, male infertility is the inability of the male reproductive cells to produce mature, actively motile and functional spermatozoa in sufficient amount that will ensure fertilization of a released ovum in the fallopian tube [2]. Usually the women are blamed of infertile marriages, especially when the man is able to achieve erection and ejaculate [2]. Since the quality of seminal fluid cannot be physically assessed, the intervention of the medical laboratory is often sought [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations